2008
DOI: 10.1111/j.1540-8159.2008.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Rhythm Restoration after Atrial Fibrillation: The Clinical Value of N‐Terminal Pro‐BNP Measurements

Abstract: With SR restoration, NTP-BNP decline is observed up to 1 month. NTP-BNP drop is partially or completely abolished by PaAF and RAF, respectively. NTP-BNP does not predict successful SR restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
2
13
0
1
Order By: Relevance
“…It was also reported that both NT-proBNP and BNP values decrease after conversion to sinus rhythm in patients with persistent AF [16,17]. Moreover, natriuretic peptides are predictive of recurrent AF after electrical cardioversion.…”
Section: Paroxysmalmentioning
confidence: 99%
“…It was also reported that both NT-proBNP and BNP values decrease after conversion to sinus rhythm in patients with persistent AF [16,17]. Moreover, natriuretic peptides are predictive of recurrent AF after electrical cardioversion.…”
Section: Paroxysmalmentioning
confidence: 99%
“…It has been also recommended that BNP increases within 4 hours from the onset of atrial inflammation; whether this applies to NT-pro-BNP is also not clear [20]. In demonstrating association between NT-pro-BNP and atrial fibrillation, it has been shown that NT-pro-BNP levels may drop after successful cardioversion of atrial inflammation [17]. Actually, the treatment of atrial inflammation can be reflected by reducing the level of NT-pro-BNP.…”
Section: Discussionmentioning
confidence: 99%
“…The association between NT-pro-BNP level and atrial fibrillation has been less studied and understood. Some studies have proved that NT-pro-BNP is increased in atrial fibrillation [16][17][18][19]. The proposed mechanisms are high frequency of atrial myocyte contraction and local atrial inflammation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Some recurrent AF patients yet had a major reduction in AF burden after ablation, which might contribute to a reduction in NT-pro-BNP. We included patients with paroxysmal AF and relatively low AF burden (mean 13.7/20; range [8][9][10][11][12][13][14][15][16][17][18][19][20]. Several of these patients had a baseline NT-pro-BNP well within the normal range, yet there was a statistically significant decrease of NTpro-BNP in patients after successful ablation which correlated with the reduction in LA volume.…”
Section: Nt-pro-bnpmentioning
confidence: 98%
“…Plasma N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) correlates with left atrial (LA) size [12] and epidemiological studies have identified it as a predictor of the development of AF [13]. Successful ablation of AF may initiate a reverse remodelling process in the atria, and LA size and NT-pro-BNP may decrease after restoration of sinus rhythm [14][15][16][17]. In this study, we aimed to investigate the relation between arrhythmia burden, left atrial size and NT-pro-BNP before AF ablation and after long-term follow-up in patients with normal left ventricular systolic function.…”
Section: Introductionmentioning
confidence: 98%